Graphene oxide reduction by standard industrial reducing agent : thiourea dioxide - Chua, Chun Kiang (2013)
The current fabrication methods of pristine graphene are not feasible for bulk production. The closest approach, which is through chemical reduction of graphene oxide to chemically reduced graphene oxide that resembles pristine graphene, has been widely adopted instead. Herein, we report a new methodology for the reduction of graphene oxide to chemically reduced graphene oxide using a common industrial reductant, thiourea dioxide. The final product has been fully characterized by X-ray photoelectron spectroscopy (XPS), transmission electron microscopy (TEM), scanning electron microscopy (SEM), Raman spectroscopy, electrochemical impedance spectroscopy (EIS), attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) and cyclic voltammetry. The microscopy techniques revealed reduced graphene of few-layered sheets. Based on the XPS analyses, a C/O ratio as high as 16.0 was achieved. The reduced graphene oxide product demonstrated a good electrochemical performance with a charge transfer resistance as low as 0.11 kΩ based on EIS measurements and a low overpotential for the oxidation of ascorbic acid. Since thiourea is a common industrial reductant, standard protocols are already in place for the waste produced from this methodology. As such, we foresee that this methodology holds the potential for industrial scale reduction of graphene oxide.